2008
DOI: 10.1016/j.febslet.2008.03.039
|View full text |Cite
|
Sign up to set email alerts
|

Lamellipodia and filopodia in metastasis and invasion

Abstract: Advances in our understanding of the mechanisms of lamellipodia and filopodia assembly have led to a better concept of how cells move, including how the actin cytoskeleton might be important for the motility of metastatic cancer cells. The cytoskeleton is a potentially interesting target for prevention of invasion and metastasis. As key proteins are uncovered which regulate the assembly of actin-based structures, these need to be considered in light of whether they represent potential invasion and metastasis p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
238
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 278 publications
(259 citation statements)
references
References 85 publications
10
238
0
2
Order By: Relevance
“…The in vitro invasive properties of both RA FLSs and DA rat FLSs studied herein correlate with in vivo radiographic and histological joint damage (20,21), making our observations clinically relevant. Additionally, we describe a mechanism of action where calcitriol interferes with the expression of MMP-1, which is a protease implicated in cartilage and bone damage in RA (35), and with cytoskeletal rearrangement and lamellipodia formation, which are required for cell motility and invasion (36). These observations support our original hypothesis that VDR stimulation could have a central role in the regulation of synovial processes implicated in cartilage and bone erosive joint damage.…”
Section: Discussionsupporting
confidence: 76%
“…The in vitro invasive properties of both RA FLSs and DA rat FLSs studied herein correlate with in vivo radiographic and histological joint damage (20,21), making our observations clinically relevant. Additionally, we describe a mechanism of action where calcitriol interferes with the expression of MMP-1, which is a protease implicated in cartilage and bone damage in RA (35), and with cytoskeletal rearrangement and lamellipodia formation, which are required for cell motility and invasion (36). These observations support our original hypothesis that VDR stimulation could have a central role in the regulation of synovial processes implicated in cartilage and bone erosive joint damage.…”
Section: Discussionsupporting
confidence: 76%
“…[2][3][4] Directed cell migration is typically described by the presence of chemoattractants, both in vivo and in vitro, associated to the activation or inhibition of sets of genes, and leading to the cytoskeleton reorganization and polarization. 5 This implies a functional asymmetry between the front and back sides generating preferential locations for cellular protrusion activity (lamellipodia and filopodia) to set the future direction of migration.…”
Section: Introductionmentioning
confidence: 99%
“…Because central regulators of the cell front are Rho family small GTP-binding proteins (Rho GTPases), including Rac and Rho, they are pivotal regulators of actin and adhesion organization and control the formation of lamellipodia (20). Rac1 is a direct regulator of the organization of lamellipodial structure (8,16). A previous study showed that Rac1 is downstream of signaling from the complex of paxillin, FAK, and vinculin in focal adhesions and cell-cell contacts (8).…”
Section: Discussionmentioning
confidence: 99%
“…We showed that Espin was colocalized with F-actin in lamellipodia. Lamellipodia are formed when cancer cells migrate on an extracellular matrix (ECM) such as the type I collagen or fibronectin matrix (16,17). The structure is induced in many biologic processes including cell migration and drives progression of cancer invasion and metastasis via dynamic remodeling of the actin cytoskeleton (18).…”
Section: Discussionmentioning
confidence: 99%